2020
DOI: 10.1016/j.jrurstud.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility-driven collective action in the context of rapid rural depopulation

Abstract: China has witnessed unprecedented and rapid urbanization which has led to the depopulation and structural collapse of many traditional rural village communities, and the decline of many collective functions such as the effective management of the public realm. In seeking to address this problem it is clear from the literature that there is considerable potential in catalyzing collective action, particularly where there is a moral imperative to act and the availability of leaders with the ability to organize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…In addition to this short‐term urbanisation and counterurbanization, the urban middle class are—in common with many other countries (see Paniagua, 2010; Paris, 2016)—seeking to leave city centres in favour of gentrifying the city margins in search of a better quality of life (Chen & Zhang, 2021; Marsden et al, 2011; Yang & Zhou, 2018). While being essentially demand‐led, this form of counterurbanization is consistent with Chinese policies to support rural revitalisation by encouraging new forms of social and financial investment in villages that have previously suffered from out‐migration (Du et al, 2019, 2020; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 55%
“…In addition to this short‐term urbanisation and counterurbanization, the urban middle class are—in common with many other countries (see Paniagua, 2010; Paris, 2016)—seeking to leave city centres in favour of gentrifying the city margins in search of a better quality of life (Chen & Zhang, 2021; Marsden et al, 2011; Yang & Zhou, 2018). While being essentially demand‐led, this form of counterurbanization is consistent with Chinese policies to support rural revitalisation by encouraging new forms of social and financial investment in villages that have previously suffered from out‐migration (Du et al, 2019, 2020; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 55%
“…As evidenced by the results of the researches of D. Santiago-Alarcon, I. MacGregor-Fors, similar processes occur with even greater intensity in European countries, in most of which the process of urbanization is superimposed on a decrease in the birth rate [11], as well asin recent decadesin China, which is reflected in the works of Geng Lin, P. Liu, H. Ubels, G.A. Wilson et al [7,9,12,13].…”
Section: Introductionmentioning
confidence: 82%
“…In another study in China, it was concluded that community-based collective action has a major role to play in the success of the management of collective goods. The study also concluded that local leadership plays an important role in the success of a cooperative (Liu et al 2020). As can be seen from the above discussion that AFC and Sahyadri farms were mostly promoted by motivated individuals and the role of local leadership played an important role in the success of the organisation.…”
Section: Comparative Analysis Of Casesmentioning
confidence: 96%